Spiritual mindfulness combination with self-regulation on the effect to vital sign and anxiety reduction among pneumonia survivors - Ayatulloh, Daviq; Prayoga, Dimas Hadi; Priyantini, Diah (Jurnal Keperawatan Padjadjaran, 2024)
Background: Pneumonia has become a scary disease since the emergence of the COVID-19 pandemic. The severity of pneumonia often causes sufferers to experience fear and causes the disease to worsen, resulting in the patient's hemodynamics becoming unstable, this condition need an intervention to make the condition better. Purpose: The purpose of this study was to analyze the effect of spiritual mindfulness combined with self-regulation in dealing with anxiety and improving vital signs in pneumonia patients. Methods: A experimental quantitative research using a quasi-experimental with pre and post-test control group design between August - October 2024 in the regional hospitals in Gresik Regency, East Java, Indonesia. Total 62 respondents recruited using consecutive sampling which were then divided into intervention and control groups. Spiritual mindfulness intervention combined with self-regulation was given with a frequency of 2 times a day for 7 full days. Vital signs measured included blood pressure, respiratory rate, pulse and SpO2 which were observed through the researcher's observation sheet and anxiety was measured using the Zung Self-Rating Anxiety Scale (SRAS). Data were analyzed using paired t-test and independent t-test, also Wilcoxon signed rank test and Mann Whitney test. Results: Spiritual mindfulness combination with self-regulation has effect to vital sign included blood pressure, respiration rate, pulse, oxygen saturation and anxiety of patient with pneumonia (p=0.000). The measurement showed the best changes or decreases in the intervention group, while the control group did not show much difference. Conclusions: Spiritual mindfulness combination with self-regulation is the effective intervention for vital sign and anxiety in pneumonia patients.